Quantitative evaluation of the three-dimensional deployment behavior of a shape memory polymer antenna. (4th September 2018) - An, Yongsan; Kim, Jinsu; Goo, Nam Seo; Kim, Yeontae; Park, Jong Kyoo; Yu, Woong-Ryeol
Abstract: The three-dimensional (3D) deployment behavior of a shape memory polymer (SMP) was quantitatively characterized using 3D shape descriptors. 3D shape descriptor is a numerical value which represents and analyzes the shape information of a given 3D shape. A 3D deployable antenna was designed and fabricated using an epoxy-based SMP. First, the folding behavior of the antenna was observed during deployment in a device. At this time, its entire shape was scanned, processed, and converted into surface data. Two-dimensional (2D) (area and circularity) and 3D (compactness and cubeness) shape descriptors were calculated from the surface data and compared to determine if the 3D folding behavior of an SMP antenna could be adequately described by 3D compactness, which represents how compactly the SMP antenna was able to fold. In addition to 2D shape information, these data provide height information, resulting in a more accurate and sensitive characterization of the folding process. Finally, the 3D deployment behavior (folding-unfolding) of the SMP antenna was analyzed using a 3D descriptor. The shape fixation and recovery ratios of the SMP antenna according to the 3D descriptor were 100% and 99.5%, respectively, whereas those values evaluated with a one-dimensional descriptor, such as uniaxial strain, were 98.0% and 79.1%, respectively. These results demonstrate that a 3D descriptor (compactness) can adequately assess shape memory performance.